Pengembangan Sistem Pengelolaan Rekam Medis Pasien Berbasis Web Studi Kasus: Klinik Dr. Syarif - Helman Taufiqurrahman; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dr. Syarif's Clinic is a clinic that is located in Samarinda City, East Borneo. The management of the patient's medical records in that clinic is still done by writing on a paper and stored inside the cupboard. As time goes on, it increases the place's needs for saving the medical records. Duplication of medical records could happen when the administration staff puts the medical records at the wrong side of the cupboard, which makes the medical records could not be found and the administration staff makes a new medical record. To solve these problems, a web-based management system of patient's medical records was developed for the intention of making the process of managing the patient's medical records easier. The system was developed using Object-Oriented Analysis & Design (OOAD) and Object-Oriented Programming (OOP) methods. The programming language that was used to develop the system is Personal Home Page (PHP) and the framework that was used is Codeigniter. The unit testing and the integration testing were done by using the white-box testing method, while the validation testing was done by using the black-box testing method. The result of unit testing and integration testing has shown that the system runs in accordance with the design that has been made. The result of the validation testing has shown that all the functional requirements have been fulfilled by the system. In other words, the result of all the testing is 100% valid and the system is worth to use.